KEADILAN DALAM SATU (INTRA) GENERASI:SEBUAH PENGANTAR BERDASARKAN TAKSONOMI KEADILAN LINGKUNGAN - Andri Gunawan Wibisana (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThis paper attempts to discuss intragenerational equity based on the taxonomy of environmental justice, i.e. distributive justice, corrective justice, procedural justice, and social justice. Based on distributive justice perspective, the paper places the polluter pays principle (PPP) and common but differentiated responsibility (CBDR) as two important legal principles in implementing intragenerational equity. Based on corrective justice perpective, the paper considers that the PPP plays an important role in implementing intragenerational equity. The paper explains the implementation of procedural justice in terms of access to participation, access to information, and legal standing. Finally, the paper observes the importance of the integration of environmental protection and social justice.IntisariTulisan ini mencoba untuk mendiskusikan lebih mendalam keadilan intra generasi dengan menggunakan taksonomi keadilan lingkungan, yaitu keadilan distributif, keadilan korektif, keadilan prosedural, dan keadilan sosial. Secara khusus, berdasarkan perspektif keadilan distributif, tulisan ini melihat adanya kaitan erat antara keadilan intra generasi dengan polluter pays principle (PPP) dan common-but-differentiated responsibility. Dalam perspektif keadilan korektif, tulisan ini melihat pentingnya PPP untuk mewujudkan keadilan intra generasi. Tulisan ini melihat perwujudan keadilan prosedural melalui hak untuk berpartisipasi dalam pengambilan keputusan, hak atas informasi, dan hak gugat. Dalam konteks keadilan sosial, tulisan menjelaskan integrasi perlindungan lingkungan dengan penciptaan keadilan sosial.